Experiencing problems in data collection by undergraduate EFL students as novice researchers - Faisal Mustafa; Merina Devira; Heri Apriadi; Bonjovi Hassan Hajan (Journal on English as a Foreign Language, 2022)
Data collection is a research process determining the validity and reliability of a study, and novice researchers have been found to experience many problems in this process. However, little study addressed the problem in data collection among these researchers. Therefore, this study was conducted to uncover problems experienced by English as a Foreign Language (EFL) undergraduate students without any previous experience in data collection. Seventeen undergraduate EFL students were assigned to collect data using a two-item questionnaire, which involved communicating with research participants before sending the questionnaire to the participants. After the data collection, they were requested to write a brief report explaining their communication with the participants and the problems they experienced. The reports written by the students were treated as the data for this research and were subjected to qualitative analysis to understand the problems they faced in the data collection. The results show that students experienced some problems in collecting the data, i.e., lack of responses, late responses, a negative response, and uncompleted questionnaires. The results of the study suggest that potential problems in data collection should be introduced to undergraduate EFL students before they conduct their undergraduate research.